A novel mutation +5904 C>T of RUNX1 site in the erythroid cell‐specific regulatory element decreases the ABO antigen expression in Chinese population. Issue 6 (5th July 2018) - Ying, Y.; Hong, X.; Xu, X.; Ma, K.; He, J.; Zhu, F.
Abstract : Background: An erythroid cell‐specific regulatory element (+5·8‐kb) in the first intron of ABO is responsible for the antigen differential expression and the regulatory activity of the element was affected by the nucleotide mutation in the +5·8‐kb region. Currently, many individuals with ABO subgroups were found in the Chinese population, but there was little information about the function of +5·8‐kb region in these individuals. Here, we studied the mechanism of the mutation in the +5·8‐kb region responsible for reducing of antigen expression in 30 ABO subtype Chinese individuals without mutation in the coding region or splicing site. Materials and methods: The nucleotide sequence of the partial intron 1 covering the +5·8‐kb site was amplified and directly sequenced. The haplotype with the novel mutation was obtained by the TOPO TA cloning. Both of the ABO promoter and the +5·8 kb regulatory element were subcloned into the basic luciferase reporter plasmid using the double endonuclease digestion. The promoter activity was examined by the dual‐luciferase report vector with K562 cells. Results: A novel nucleotide substitution +5904 C>T located at RUNX1‐binding site in the +5·8 kb site was identified from three individuals with B subtypes. +5890 T>G were found in three Bel and one Ael phenotypes. Cotransfection and luciferase assays demonstrated that the +5904 C>T could obviously reduce activity of the +5·8 kb site. Conclusion: The study suggested that the transcriptional activity of the +5·8 kb site could be downregulated by the single point mutation of RUNX1 motif, leading to reduction in A or B antigen expression.